ANALISIS ASUHAN KEPERAWATAN KELUARGA PADA LANSIA HIPERTENSI MELALUI INTERVENSI INOVASI HATHA YOGA UNTUK MENURUNKAN TEKANAN DARAH DI RT 06 RW 08 KELURAHAN GROGOL DEPOK - Sondang Mariani (2023)
Elderly is a group that dominates hypertension sufferers in Indonesia. Hypertension is a disease that is a threat to the world because it kills more people every year. An alternative to improving the well-being of hypertensive elderly people is doing hatha yoga because this gentle rhythm exercise can improve blood circulation and lower blood pressure. This study aims to determine the effectiveness of hatha yoga therapy in reducing blood pressure in elderly people with hypertension. This study was designed in a quasi-experimental for 8 meetings with pre-test and post-test blood pressure measurements in managed patients. Observation of blood pressure was measured using a digital sphygmomanometer. The results of the study showed that there was a significant reduction in blood pressure in managed patients, the blood pressure of patients who were managed before practicing hatha yoga was 160/94 mmHg down to 125/85 mmHg. Based on these findings, it becomes a suggestion for nurses to be able to carry out alternative non-pharmacological management of hatha yoga for elderly hypertension.